Manual de procedimientos administrativos para el óptimo funcionamiento de la Terminal Terrestre "Quinche J. Félix " de la ciudad de Calceta. - Rodríguez Zambrano, Jorge Eduardo (2011)
The present investigation carried out at the bus terminal located in the city of calceta, for a period of six months. The purpose for this investigation consisted on the designing of a manual of procedure for office workers which would provide them the best knowledge on how the Terminal Terreste Quinche J. Félix should function. therefore, it was necessary to determine the current procedure of the administrative system of the institution. The level of satisfaction and preference of the population was agreed on. the necessary administrative procedures were designed to provide the highest quality of service on how the institution should function. Finally the manual was given to the officials to review and it was accepted since the institution lacked a tool which allowed them to use based on a document structured for the administrative procedures. In the investigative work, scientic methods were applied, such as, field work which allowed the obsevation and the detection on how the administrative procedure are applied along with the bibliographical investigation and the historical method that allowed us the knowledge to get to know the administrative evolution of the institution. In addition there were exsisting procedures which fuctioned for the necessity of the institution although they were not within the norms. So, a manual of procedures was created with an easy method of design to use and understand, which offers the knowledge of the methods that the employees of the institution should develope. Finally it was determined that this manual should be provided to officials and employees of the terminal Terrestre Quinche J. Félix.